Lower omental t‐regulatory cell count is associated with higher fasting glucose and lower β‐cell function in adults with obesity. Issue 6 (2nd May 2016) - Gyllenhammer, Lauren E.; Lam, Jonathan; Alderete, Tanya L.; Allayee, Hooman; Akbari, Omid; Katkhouda, Namir; Goran, Michael I.
Abstract : Objective: T‐lymphocytes are potential initiators and regulators of adipose tissue (AT) inflammation, but there is limited human data on omental AT. The aim of this study was to assess the relationship between T cells, particularly Foxp3+ regulatory T (Treg) cells, in human subcutaneous (subQ) and omental AT and type 2 diabetes risk. Methods: SubQ and deep subQ (DsubQ) abdominal and omental AT biopsies were collected from 44 patients (body mass index, BMI ≥25) undergoing elective abdominal surgery. Flow cytometry was used to quantify CD4+ T cell (T effector and Treg) and macrophages (M1 and M2), and systemic inflammation was measured in fasting blood. Results: Tregs were significantly lower in omental versus subQ and DsubQ AT, and M1 cell counts were significantly higher in the omental and DsubQ depot relative to the subQ. Only omental AT Tregs were negatively associated with fasting glucose and MCP‐1 and positively associated with homeostasis model assessment (HOMA)‐β. M1 and M2 cell counts across multiple depots had significant relationships with HOMA‐insulin resistance, tumor necrosis factor‐α, insulin, and HOMA‐β. All relationships were consistent across ethnicities. Conclusions: Tregs were significantly lower in omental versus both subQ adipose depots. Fewer omental Tregs may have metabolic implications based on depot‐specific relationships with higher fasting glucose and lower β‐cell function.